2011
DOI: 10.1016/j.pain.2010.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention to thermal pain stimuli in subjects with visual spatial hemi-neglect: Extinction, mislocalization and misidentification of stimulus modality

Abstract: One approach to the study of disordered spatial attention is to carry out tests of extinction, in which stimuli are detected on the left when they are presented on the left alone, but not when both sides are stimulated simultaneously in a dual simultaneous stimulation (DSS) protocol. Extinction has been documented for multiple sensory modalities, but not for thermal pain stimuli, to our knowledge. We now test the hypothesis that subjects with visual spatial neglect (hemi-neglect) will have alterations in therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Complementary to previous descriptions of hemianesthesia after right brain damage [14], Liu et al [11] described two patients with nociceptive extinction. These patients were able to report correctly the occurrence of a nociceptive stimulus when it was applied to their contralesional hand alone.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…Complementary to previous descriptions of hemianesthesia after right brain damage [14], Liu et al [11] described two patients with nociceptive extinction. These patients were able to report correctly the occurrence of a nociceptive stimulus when it was applied to their contralesional hand alone.…”
mentioning
confidence: 71%
“…For example, it has been shown that covert movement of spatial attention on the body can modify the whole cortical processing of nociceptive stimuli [9]. Even more striking evidence is provided in the present issue of PAIN® by Liu et al [11], who studied detection of nociceptive stimuli in braindamaged patients with a neglect syndrome. Neglect denotes the impaired ability to process or to respond to sensory stimuli presented in the hemiportion of space contralateral to the side of the lesion (most often in the right hemisphere) [4].…”
mentioning
confidence: 72%
See 3 more Smart Citations